Neuropsychological Functioning in Patients with Cushing’s Disease and Cushing’s Syndrome - Siegel, Sonja; Kirstein, Cedric Fabian; Grzywotz, Agnieszka; Hütter, Bernd Otto; Wrede, Karsten Henning; Kuhna, Victoria; Kreitschmann-Andermahr, Ilonka (Experimental and Clinical Endocrinology & Diabetes, 2020)
Purpose To present a systematic review of the presence and severity of neuropsychological impairment in the six main neuropsychological domains (attention, executive function, language, visuospatial processing, intelligence, and memory) in patients with Cushing’s disease (CD) and/or Cushing’s Syndrome (CS) at various stages of the illness. The work aims to identify neuropsychological leverage points for focused diagnosis and rehabilitation in CS/CD patients.Methods A pubmed literature search was performed and augmented by searching the reference lists of review articles identified by this search strategy. After excluding irrelevant hits, we systematically extracted data from 27 studies for each main neuropsychological domain, differentiating between active disease, short- and long-term remission.Results The literature gives evidence for neuropsychological impairment in all domains in Cushing patients with active disease. The most consistent impairments concerned memory and visuo-spatial processing, whereas the data are discordant for all other domains. Significant improvement of neuropsychological function – although not returning to normal in all domains – is shown in short-term and long-term remission of the disease. However, the published literature is thin, suffering from repetitive subsample analyses publishing, methodological concerns as lack of control for confounders such as depression.Conclusions Memory is the most extensively investigated domain in CS/CD patients and impairment is most prominent in active disease. Patients should be counseled that neuropsychological function will improve with normalization of hypercortisolism and over time. More studies with more stringent methodological criteria, larger patient samples and controlling for confounders are required to enhance our understanding of neuropsychological function in patients with CS/CD.
Keywords: Cushing’s disease; Cushing’s syndrome; neuropsychological impairment; depression; rehabilitation